The Impact of Internationalization in Influencing Firm Performance and Competitive Advantage: The Mediating Role of Eco-Innovation - Sri Juniati; Mohd Haizam Mohd Saudi; Eriana Astuty; Norhisham Abdul Mutalib (International Journal of Supply Chain Management, 2019)
The aim of this study is to examine the impact of internationalization, on firm performance and competitive advantage in Malaysia multinational companies. In doing so, we utilized of Exploratory Factor Analysis (EFA) to find the four factors are depicted by aggregate twenty-four items in which all items factor loadings are more noteworthy than 0.70. Besides, the consequences of estimation model wellness of CFA clarify that every of the four considered model wellness clarify that the gathered data is fit for making the factors. Finally, the outcomes of structural equation modelling prescribed that at first, four constructs eco-innovation (includes organization eco-innovation, process eco-innovation and product eco-innovation), internationalization and firm performance successfully predict competitive advantage. Moreover, firm performance, eco-innovation and internalization have a positive and significant impact on competitive advantage in Malaysian multinational firms. Furthermore, our results also confirm that eco-innovation has significantly mediates the relationship between internationalization and firm performance. This model clarifies 63.38% variation of competitive advantage by internationalization, firm performance and eco-innovation in Malaysia MNC’s.